Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the equation of the line that is perpendicular to the given line [tex]\( 2x + 12y = -1 \)[/tex] and passes through the point [tex]\((0, 9)\)[/tex], follow these steps:
1. Convert the given line to slope-intercept form ( [tex]\( y = mx + b \)[/tex] ):
Start with the given equation:
[tex]\[ 2x + 12y = -1 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 12y = -2x - 1 \][/tex]
Divide by 12:
[tex]\[ y = -\frac{2}{12}x - \frac{1}{12} \][/tex]
Simplify the expression:
[tex]\[ y = -\frac{1}{6}x - \frac{1}{12} \][/tex]
So, the slope [tex]\( m_1 \)[/tex] of the given line is [tex]\( -\frac{1}{6} \)[/tex].
2. Find the slope of the line perpendicular to the given line:
The slope of a line perpendicular to another is the negative reciprocal of the original line's slope. Therefore:
[tex]\[ m_2 = -\frac{1}{-\frac{1}{6}} = 6 \][/tex]
3. Use the point-slope form of the line equation:
The point-slope form is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\((x_1, y_1)\)[/tex] is the point the line passes through. In this case, the point is [tex]\((0, 9)\)[/tex]:
Substitute [tex]\( m_2 = 6 \)[/tex], [tex]\( x_1 = 0 \)[/tex], and [tex]\( y_1 = 9 \)[/tex] into the equation:
[tex]\[ y - 9 = 6(x - 0) \][/tex]
Simplify the equation:
[tex]\[ y - 9 = 6x \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = 6x + 9 \][/tex]
So, the equation of the line that is perpendicular to [tex]\( 2x + 12y = -1 \)[/tex] and passes through the point [tex]\((0, 9)\)[/tex] is:
[tex]\[ y = 6x + 9 \][/tex]
Hence, the correct answer is:
[tex]\[ y = 6x + 9 \][/tex]
1. Convert the given line to slope-intercept form ( [tex]\( y = mx + b \)[/tex] ):
Start with the given equation:
[tex]\[ 2x + 12y = -1 \][/tex]
Solve for [tex]\( y \)[/tex]:
[tex]\[ 12y = -2x - 1 \][/tex]
Divide by 12:
[tex]\[ y = -\frac{2}{12}x - \frac{1}{12} \][/tex]
Simplify the expression:
[tex]\[ y = -\frac{1}{6}x - \frac{1}{12} \][/tex]
So, the slope [tex]\( m_1 \)[/tex] of the given line is [tex]\( -\frac{1}{6} \)[/tex].
2. Find the slope of the line perpendicular to the given line:
The slope of a line perpendicular to another is the negative reciprocal of the original line's slope. Therefore:
[tex]\[ m_2 = -\frac{1}{-\frac{1}{6}} = 6 \][/tex]
3. Use the point-slope form of the line equation:
The point-slope form is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\((x_1, y_1)\)[/tex] is the point the line passes through. In this case, the point is [tex]\((0, 9)\)[/tex]:
Substitute [tex]\( m_2 = 6 \)[/tex], [tex]\( x_1 = 0 \)[/tex], and [tex]\( y_1 = 9 \)[/tex] into the equation:
[tex]\[ y - 9 = 6(x - 0) \][/tex]
Simplify the equation:
[tex]\[ y - 9 = 6x \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = 6x + 9 \][/tex]
So, the equation of the line that is perpendicular to [tex]\( 2x + 12y = -1 \)[/tex] and passes through the point [tex]\((0, 9)\)[/tex] is:
[tex]\[ y = 6x + 9 \][/tex]
Hence, the correct answer is:
[tex]\[ y = 6x + 9 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.